Morphology of Electrospun Non-Woven Membranes of Poly(vinylidene fluoride-co-hexafluoropropylene): Porous and Fibers - Dognani, Guilherme [UNESP]; Cabrera, Flávio Camargo [UNESP]; Job, Aldo Eloizo [UNESP]; Agostini, Deuber Lincon da Silva [UNESP] (Springer Nature, 2019)
In this paper, poly(vinylidene fluoride-co-hexafluoropropylene) nanofibers membranes were fabricated by facile single-capillary electrospinning at different times of production. The materials were characterized by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), atomic force microscopy (AFM), contact angle (CA), mercury porosity intrusion (MIP), Tensile tests, capillary flow porosity (CFP) and, BET surface by nitrogen adsorption-desorption. The membranes were fabricated varying the fibers density, the thickness and the morphology. The samples presented a good fiber diameter distribution and an average diameter of 321 nm. AFM results showed high porosity (82.7-87.5 %), a high contact angle of 159.2°, mean pore size of 0.637 μm and hydrophobicity of the membranes. A low value of permeate pure water flux, 5.2 %, was observed for the densest fabricated membrane. The porosity of fibers diameters was similar for all samples, which is an important parameter as they can be potential materials for membrane distillation process.
Keywords: Elelctrospinning; Fibers; Membrane; Morphology; Porous material